Navigating the New Landscape: Consumer Rights and Halal Product Guarantees in Indonesia - Kerti, Renti Maharaini (UNISSULA, 2025)
Rising public awareness of halal certification and consumer rights in Indonesia has prompted strengthened regulations through Law Number 33 of 2014 on Halal Product Assurance, aiming to ensure compliance with Islamic standards and protect Muslim consumers. This study examines how this law impacts consumer trust, market dynamics, and business readiness, particularly for micro, small, and medium enterprises, while addressing gaps in regulatory enforcement and consumer awareness. Employing a qualitative approach with a descriptive-analytical design, data were gathered through in-depth interviews with stakeholders, including certification bodies, businesses, and consumers, alongside document reviews and observations. Findings reveal that the law enhances consumer confidence in halal product authenticity but imposes significant administrative and financial burdens on small businesses, especially in rural areas, due to centralized certification processes and high costs. Limited consumer understanding of certification procedures and weak oversight mechanisms increase risks of fraudulent labeling. Digitalizing certification processes and integrating halal information into e-commerce platforms can improve transparency and accessibility, though effectiveness depends on institutional capacity and stakeholder collaboration. The study concludes that a balanced, inclusive halal ecosystem requires robust policy support, empowerment of small businesses, and enhanced consumer education to ensure regulatory success and global competitiveness.